Development of the 5E-POW (Predict–Observe–Write) Learning Model Assisted by Virtual Simulation to Reduce Pre-service Teacher Misconceptions on the Topic of Fluids - Oka Saputra; Aisyah Nur Fadillah; Hanandita Veda Saphira (Universitas Ahmad Dahlan, 2025)
Misconceptions about fluid mechanics are persistent and require instructional strategies by which conceptual conflict, reflection, and visualization are integrated. In this study, a virtual simulation-assisted 5E-POW (Predict–Observe–Write) learning model was developed and preliminarily implemented to reduce pre-service teachers’ misconceptions about fluid mechanics. The ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation, was employed. The preliminary implementation involved 18 pre-service teachers from the 2024 cohort. Data were collected using expert validation sheets and a 29-item four-tier diagnostic test administered before and after implementation. The data were analyzed using validity analysis, misconception reduction analysis, normality testing, and a paired-samples t-test. The developed learning model, learning instruments, and virtual simulation media met the validity criteria, although minor revisions to the simulation media were required. Following implementation, decreases in misconception percentages were found for hydrostatic pressure (49.71%), Pascal’s law (35.20%), Archimedes’ principle (49.34%), discharge and continuity (47.00%), and Bernoulli’s principle (55.00%). The pretest and posttest data were normally distributed, and a significant difference was found between the two measurements. These findings indicate that the developed model is feasible and shows potential for reducing pre-service teachers’ misconceptions about fluid mechanics. Its contribution lies in integrating the 5E Learning Cycle, the POW strategy, and virtual simulation into a single instructional framework. Further controlled studies with larger samples are required to establish its effectiveness.